Calcium and cell death signaling in neurodegeneration and aging - Smaili,Soraya (2009)
Transient increase in cytosolic (Cac2+) and mitochondrial Ca2+ (Ca m2+) are essential elements in the control of many physiological processes. However, sustained increases in Ca c2+ and Ca m2+ may contribute to oxidative stress and cell death. Several events are related to the increase in Ca m2+, including regulation and activation of a number of Ca2+ dependent enzymes, such as phospholipases, proteases and nucleases. Mitochondria and endoplasmic reticulum (ER) play pivotal roles in the maintenance of intracellular Ca2+ homeostasis and regulation of cell death. Several lines of evidence have shown that, in the presence of some apoptotic stimuli, the activation of mitochondrial processes maylead to the release of cytochrome c followed by the activation of caspases, nuclear fragmentation and apoptotic cell death. The aim of this review was to show how changes in calcium signaling can be related to the apoptotic cell death induction. Calcium homeostasis was also shown to be an important mechanism involved in neurodegenerative and aging processes.